Vertically aligned 2D carbon doped boron nitride nanofilms for photoelectrochemical water oxidation. Issue 26 (29th June 2020) - Fang, Yuanxing; Merenkov, Ivan S.; Li, Xiaochun; Xu, Junkang; Lin, Sen; Kosinova, Marina L.; Wang, Xinchen
Abstract : 2D carbon-doped boron nitride nanofilms are vertically aligned on conductive glass to create a photoanode for solar-driven water oxidation. This photoanode shows an improved performance compared to that of a powder based photoanode. Abstract : Metal-free photocatalysis has evoked broad research interest in green energy applications. Herein, two-dimensional (2D) carbon-doped BN (C-BN) nanosheets are vertically aligned on a conductive substrate by low-temperature plasma enhanced chemical vapor deposition (PE-CVD) and are demonstrated to be a photoelectrocatalytic device for water oxidation under sunlight irradiation. By virtue of this geometry, the unique 2D material presents advantages for the catalytic reaction. In addition, adjusting the carbon concentration can facilely control the structure and optoelectronic properties of the C-BN nanosheets to improve light harvesting in the solar spectrum. As a result, the photocurrent density exhibits a 60-fold enhancement over that of the C-BN films achieved by traditional deposition of C-BN powder. Experimental and theoretical studies of band structures are performed and the results are in agreement with each other. This 2D C-BN nanofilm based device could stimulate interest in advanced applications in many fields such as catalysis, sensors, transistors and others.